Seeing God and Becoming Blessed: Μακαριότης, Purification, and the Hermeneutic Possibilities of "Scholium 136 in Proverbium" 14, 9 by Evagrius Ponticus - de Pina Almeida Prado, Henrique (Vox Patrum, 2026)
In this article, it is argued that the different verbs designating vision, as attested in MS Patmiacus 270, MS Vaticanus Graecus 1802, codices Iviron 38, Iviron 379, Iviron 676, and Parisinus Graecus 153 are central to Evagrian hermeneutics. These choices have a great impact on Evagrius’ theology, concerning not only the vision of God but also another concept deeply rooted in this kind of vision: μακαριότης. While MS Patmiacus 270 attests the verb ὄψωνται as designating vision, codices Iviron 38, Iviron 379, Iviron 676, Parisinus Graecus 153, and MS Vaticanus Graecus 1802 attest ἴδωσι. One might think that both verbs could be used interchangeably. However, deeper research indicates that the different readings might entail different theological ideas. On the one hand, verbs with the stem ἰδ-—at least in Evagrius’ corpus—generally indicate the sort of natural vision shared even with demons, which is likely to rule out the vision of God. On the other hand, verbs with the stem ὀψ- are often used to indicate supernatural vision or even the vision of God. Furthermore, the reading ὄψωνται in the "Scholium 136 in Proverbium" 14, 9 may constitute a lectio difficilior to be considered in new editions.